Utilization of Patient-Reported Outcomes to Guide Symptom Management during Stereotactic Body Radiation Therapy for Clinically Localized Prostate Cancer - Danner, Malika; Hung, Ming-yang; Yung, Thomas M.; Ayoob, Marilyn; Lei, Siyuan; Collins, Brian T.; Suy, Simeng; Collins, Sean P. (Frontiers in Oncology, 2017)
Introduction: Utilization of patient-reported outcomes (PROs) to guide symptom management during radiation therapy is increasing. This study focuses on the use of the Expanded Prostate Cancer Index Composite for Clinical Practice (EPIC-CP) as a tool to assess urinary and bowel bother during stereotactic body radiation therapy (SBRT) and its utility in guiding medical management. Methods: Between September 2015 and January 2017, 107 patients with clinically localized prostate cancer were treated with 35-36.25 Gy via SBRT in 5 fractions. PROs were assessed using EPIC-CP one hour prior to the first fraction (baseline) and after each subsequent fraction. Symptom management medications were prescribed based on physician clinical judgment or if patients reported a moderate to big problem. Clinical significance was assessed using a minimally important difference (MID) of 1/2 SD from baseline score. Results: A median baseline EPIC-CP urinary symptom score of 1.5 significantly increased to 3.7 on the day of the final treatment (p <0.0001). Prior to treatment, 9.3% of men felt their overall urinary function was a moderate to big problem that increased to 28% by the end of the fifth treatment. A median baseline EPIC-CP bowel symptom score of 0.3 significantly increased to 1.4 on the day of the final treatment (p <0.0001). Prior to treatment, 1.9% of men felt their overall bowel function was a moderate to big problem that increased to 3.7% by the end of the fifth treatment. The percentage of patients requiring an increased dose of alpha-antagonist increased to 47% by the end of treatment and an additional 28% of patients required a short steroid taper to manage moderate to big urinary problems. Similarly, the percentage of patients requiring anti-diarrheals reached 12% by the fifth treatment. Conclusion: During the course of SBRT, an increasing percentage of patients experienced clinically significant symptoms many of which required medical management. Monitoring patient symptoms during treatment allowed for prompt detection and management of acute urinary and bowel symptoms. The usage of symptom management medications was high in this study as compared to historical controls and may be due to increased physician awareness of moderate to big patient problems.